COVID-19 on an acute psychiatric unit: an interdisciplinary, trauma-informed response. Issue 1 (2nd March 2022) - Carroll, Laura; Casey, Hannah; Adams, Rory; O'Connor, Stephanie; O'Reilly, Áine
Abstract : Purpose: There is a high prevalence of trauma among mental health clients, with risk of re-traumatisation when admitted to a Department of Psychiatry (DoP) (Kimberg and Wheeler, 2019). The COVID-19 pandemic poses challenges to therapy service operations in DoPs, with infection control measures impacting opportunities for therapeutic and social engagement. A trauma-informed care (TIC) lens was used when adapting services in Tallaght University Hospital DoP in response to COVID-19. Design/methodology/approach: An interdisciplinary approach was taken to adapt therapy services during early stages of the pandemic. Changes were informed by TIC principles to minimise re-traumatisation while maintaining high-quality services. Changes included expansion of the therapeutic activity programme, changes to groups, addition of COVID-19-specific groups and increased awareness of communication support needs. Findings: The early response to the pandemic, combined with the focus on TIC, resulted in continued, effective therapy services and positive client feedback. With clients' involvement in their care enhanced, Individual Care Planning goals were achieved through group interventions. Originality/value: The COVID-19 pandemic brought unprecedented changes to mental health services. This paper highlights a response to unique challenges brought by COVID-19 on a DoP.